2000
DOI: 10.1002/j.2050-0416.2000.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Malt Performance is More Related to Inhomogeneity of Protein and β-Glucan Breakdown than to Standard Malt Analyses

Abstract: Nitrogen analyses of the grains of samples of commercial malts indicate that fi-glucan breakdown and the uniformity of malt modification are influenced by uniformity of distribution of grain protein. It is proposed that for normal malting barley, variations in malt modification are related to the different percentages of grains which contain high levels and different types of proteins which resist enzymic modification during malting. This kind of inhomogeneity of malt modification can cause brewhouse problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 2 publications
1
31
0
1
Order By: Relevance
“…V ročníkoch s priaznivým priebehom poveternostných podmienok sa v zrne pozastaví hlavne tvorba sacharidov a zrno sa stáva bohaté na dusíkaté, hlavne nebielkovinové látky [13]. Podľa viacerých autorov obsah hrubého proteínu sa nedá ovplyvniť výberom odrody, lebo viac ako 80 % premenlivosti tohto znaku je ovplyvnený agroekologickými podmienkami ročníka [15,6,7].…”
Section: úVodunclassified
“…V ročníkoch s priaznivým priebehom poveternostných podmienok sa v zrne pozastaví hlavne tvorba sacharidov a zrno sa stáva bohaté na dusíkaté, hlavne nebielkovinové látky [13]. Podľa viacerých autorov obsah hrubého proteínu sa nedá ovplyvniť výberom odrody, lebo viac ako 80 % premenlivosti tohto znaku je ovplyvnený agroekologickými podmienkami ročníka [15,6,7].…”
Section: úVodunclassified
“…It has been shown that it is the rate of cell wall modification of individual barley grains that determines the overall rate of the malting process and the quality of the malt. 7,23 Consequently, in the development of improved malting barley germplasm it is important to take into account the uniformity as well as the rate of modification. However, the degree of homogeneity of malting barley cannot be assessed using traditional methods of analysis, which are based on the average properties of a sample.…”
Section: Potential For Testing For Homogeneity Of Barley Grains With mentioning
confidence: 99%
“…Any measure of nitrogen content made on a sample from the crop is thus a mean value of the individual grains within that sample. Even though that mean value falls within an acceptable range for malting, if the population demonstrates wide or uneven distribution around the mean, the sample can give problems in the brewhouse 17 . This is compounded by the fact that commercial maltings now operate on a very large scale 26 , so barley from several (or many) field crops will be malted together.…”
Section: Introductionmentioning
confidence: 98%